Support for The Use of Vacant Land for Catfish Farming with Simple Media as an Effort to Increase Community Food Security - Tjetjep Yusuf Afandi; Elis Irmayanti; Zainal Arifin; Bayu Surindra; Efa Wahyu Prastyaningtyas; Eunike Rose Mita Lukiani; Nina Dyah Ayu Palupi; Fredo Ladona Alamsyah; Ari Saputri Novita Anggraini (International Journal of Community Service Implementation, 2024)
Community support activities in using vacant land for catfish farming using simple media in Genengan Hamlet RT.06 / RW.04, Sambiresik Village make it a community opportunity to improve food security and economic improvement. Catfish farming was chosen because it has several advantages including a quick harvest period, catfish are resistant to disease and the culture media can be varied. The purpose of this service is to educate and guide the community in Genengan Hamlet RT.06 / RW.04, Sambiresik Village to overcome the problem of vacant and narrow land for catfish farming using simple media that is effective and efficient. This service uses five methods including socialization, training and practice, mentoring, monitoring and evaluation, which through direct involvement in the community will provide solutions and training steps in detail so that they are easily understood. The results of this service are that the community is increasingly improving their skills in using vacant land, so an increase in food security and community income is expected from this activity to create new jobs and develop local industries through catfish farming.